2008
DOI: 10.1007/s10165-008-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone versus triamcinolone in painful shoulder using ultrasound-guided injection

Abstract: There is little evidence about the comparative efficacy of corticosteroids in the treatment of painful shoulder. The main aim was to compare the efficacy of methylprednisolone (MTP) versus triamcinolone (TMC) in the treatment of painful shoulder using an ultrasound-guided injection. Patients with painful shoulder due to subacromial bursitis and partial or full-thickness rotator cuff tears demonstrated by musculoskeletal ultrasound received a guided-injection of MTP acetate 40 mg (12 patients) or TMC acetonide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Most studies [28‐42] show small improvements in pain and functional outcomes for several weeks after steroid injection into the subacromial space compared to alternative treatments (physical therapy, oral nonsteroidal anti‐inflammatory drugs, microwave diathermy, lidocaine injection, saline solution) for the treatment of pain and functional disability due to rotator cuff impingement syndrome, whereas several others [43‐49] show no relative difference. In 3 studies that used ultrasound guidance during the subacromial space injection [35,36,42], positive results were observed in the steroid groups compared to the placebo groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies [28‐42] show small improvements in pain and functional outcomes for several weeks after steroid injection into the subacromial space compared to alternative treatments (physical therapy, oral nonsteroidal anti‐inflammatory drugs, microwave diathermy, lidocaine injection, saline solution) for the treatment of pain and functional disability due to rotator cuff impingement syndrome, whereas several others [43‐49] show no relative difference. In 3 studies that used ultrasound guidance during the subacromial space injection [35,36,42], positive results were observed in the steroid groups compared to the placebo groups.…”
Section: Resultsmentioning
confidence: 99%
“…Chavez‐Lopez et al [34] compared subacromial space injection of 40 mg methylprednisolone acetate to 40 mg triamcinolone acetonide for the treatment of rotator cuff impingement. At 2 weeks, 92% (95% CI = 62%‐100%) of participants in the methylprednisolone group reported a pain reduction of 50% or greater compared to only 50% (95% CI = 21%‐79%) of the participants in the triamcinolone acetonide group ( P = .02).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, most physicians tended to use the same corticosteroid for all injections, regardless of joint location. Triamcinolone and methylprednisolone have been compared directly in a few studies, with similar efficacy reported between triamcinolone acetate and methylprednisolone acetate 22‐26 . Thus physicians may simply choose a single medication for a particular reason (cost, comfort, convenience, formulary, and so on) and continue to use it exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid injection is certainly superior to PT in reducing pain but evidence is conflicting regarding restoration of ROM while comparing steroid injection with PT or MUA [46]. Furthermore, many issues regarding use of local injectable steroids such as optimal dose [52,53], single or multiple injection, site of injection (intraarticular/subacromial/rotator interval) [54,55], molecule (Triamcinolone/Methylprednisolone) [56][57][58], injection with or without imaging [59] remain contentious and are briefly mentioned in Table 1.…”
Section: Non-operative Treatment Of Frozen Shouldermentioning
confidence: 99%